2005
DOI: 10.4081/monaldi.2005.646
|View full text |Cite
|
Sign up to set email alerts
|

The relation of the pleural thickening in tuberculosis pleurisy with the activity of adenosine deaminase

Abstract: Selvi, A. Kant, S. Arslan, M. Ozgel. Background: Residual pleural thickening (RPT) still occurs in most patients with tuberculosis pleurisy despite advances in the treatment of tuberculosis. The aim of this study was to evaluate the significance of RPT in tuberculosis pleurisy with the patients clinical findings, biochemical and microbiological properties of pleural effusion and with the total adenosine deaminase (ADA) and isoenzymes levels. Methods: 121 tuberculosis pleurisy patients were evaluated retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
2
8
2
Order By: Relevance
“…The prevalence of RPO in the present study was higher compared with previous studies (2-4, 7, 17, 18). We cannot explain this appropriately although there was a possibility that it originated from selection bias.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of RPO in the present study was higher compared with previous studies (2-4, 7, 17, 18). We cannot explain this appropriately although there was a possibility that it originated from selection bias.…”
Section: Discussioncontrasting
confidence: 92%
“…Loculation on CT also implies the chronicity of the pleural effusion. Furthermore, longer symptom duration was a marginal but significant predictor on the formation of TPE, which supports the results of the study by Barbas et al (3, 17). …”
Section: Discussionsupporting
confidence: 91%
“…In recent years, the mechanism of pleural thickening and adhesion has been controversial. Some researchers present that the pleural thickening degree is associated with elevated protein and adenosine deaminase (ADA) in pleural effusion [7]. While some researchers oppose this view, and instead present that the decrease of PH and glucose in the thoracic liquid is associated with pleural thickening [8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its diagnostic utility varies considerably across different geographical regions, clinical settings and test result thresholds (Salmanzadeh et al, 2015). Even though the most widely accepted threshold ADA value is 35-40 U/L, some studies suggested lower cutoffs should be considered in elderly population since ADA decreases with age (Uskul et al, 2005).…”
Section: Introductionmentioning
confidence: 99%